Clínica de linguagem com afásicos: sintoma, queixa e demanda - Cesar, Maria Fernanda Cestari de (2017)
The subject matters dealt with in this study are clinical in their nature since it was stimulated by three different patients’ abandonment of treatment, which led me to reflect on the problem of patient's commitment to therapy. It is well known that such a commitment is strictly linked to the relationship between the complaint – demand related notions. Concerning the “complaint” it is expected that patient offers reasons for his suffering when he tries to say "what he has". In the Language Clinic, suffering has to do with (is caused) a symptom in speech, i.e., to an unbearable pain related to speech. The “demand”, in its turn, is the request made to the other therapist, to whom the patient supposes knowledge about his symptomatic condition. In the present work, I approach themes related to the aphasic symptom; to case study presentations in the clinical literature (medical, psychoanalytical) and, of course, to complaint and demand in the Language clinic with aphasic patients. I bring Freud (1891) to oppose his notion of symptom in aphasia to the medical viewpoint on the subject - a deep difference that is of great relevance for the Language Clinic. Fonseca (1995) pioneered the criticism concerning the organicist discourse on aphasia which supports the idea that symptoms in speech are directly caused by the cerebral damage. She postulated that, for a language therapist, aphasia is basically a language problem that affects the aphasic speaker. The author proposes clinical procedures consistent with that statement. Following this trend of thought, I considered important to discuss the question: "what is a clinical case". In other words, I tried to demonstrate how case studies are approached in the medical field and in the psychoanalytic field and presented a brief overview of how "cases" (clinical materials) have been dealt and written in the Language Clinic with aphasics. Finally, I present and discuss segments of therapies conducted by. They were the start-point for the present study